2017
DOI: 10.3892/ijmm.2017.2934
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in the progression of osteoarthritis: The autophagy inhibitor, 3-methyladenine, aggravates the severity of experimental osteoarthritis

Abstract: Accumulating evidence suggests that autophagy is closely related to the pathogenesis of osteoarthritis (OA). The aim of this study was to determine the changes in autophagy during the progression of OA and to elucidate the specific role of autophagy in OA. For this purpose, a cellular model of OA was generated by stimulating SW1353 cells with interleukin (IL)-1β and a rabbit model of OA was also established by an intra-articular injection of collagenase, followed by treatment with the autophagy specific inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…Impaired autophagy has been found in various degenerative diseases, including Alzheimer's disease 17 , osteoarthritis 18 and macular degeneration 19 . These findings may highlight the role of autophagy in sustaining function of different cells in various tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired autophagy has been found in various degenerative diseases, including Alzheimer's disease 17 , osteoarthritis 18 and macular degeneration 19 . These findings may highlight the role of autophagy in sustaining function of different cells in various tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This process compromises the ability of the chondrocytes to maintain and repair the articular cartilage tissue [ 5 , 6 ]. Chondrosenescence, with the prevailing harmful biomechanical stress, leads to irreversible chondrocyte cell death, which ultimately leads to cartilage damage, matrix depletion and loss of cartilage cellularity [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the occurrence of OA is related to the decline of chondrocyte autophagy level [23]. Besides, animal studies have also found that inhibition of autophagy of chondrocytes significantly aggravated the degeneration of chondrocytes and cartilage in osteoarthritis and promoted the occurrence of OA [40]. Besides, some studies have found that in the early stage of OA, the expression of LC3 and atg5 in osteoarthritis chondrocytes were increased, suggesting that autophagy was enhanced [41].…”
Section: Discussionmentioning
confidence: 99%